История оспопрививания в Таврической губернии во второй половине XIX - начале XX вв. (по материалам губернского и уездных земских собраний) - Масленникова, В.А. (Культура народов Причерноморья, 2014)
В статье описана история оспопрививания в Таврической губернии по материалам
губернских и уездных земских собраний. Рассмотрены и основные проблемы, препятствующие
оспопрививанию, такие как: халатность властей, недостаток медперсонала, недостаточная
квалификация оспопрививателей, плохое качество детрита. Дана общая оценка санитарно-
гигиеническому состоянию губернии. Показано отношение население к оспопрививанию. Составлен
график, показывающий зависимость болеющих оспой от прививок. Раскрыт вопрос о финансировании. В
статье перечислены поставщики детрита в губернию. У статті описана історія вакцинаціi Таврійській губернії за матеріалами губернських і
повітових земських зборів. Розглянуто основні проблеми, що перешкоджають якістноi вакцинаціi, такі
як: недбалість влади, брак медперсоналу, недостатня кваліфікація оспопрівівателей, погана якість
детриту. Дана загальна оцінка санітарно-гігієнічному станом губернії. Показано ставлення населення
до віспощеплення. Складено графік, що показує залежність хворіють віспою від щеплень. Розкрито
питання про фінансування. У статті перераховані постачальники детриту в губернію. The article describes the basic methods of smallpox vaccination and history of beginning of
vaccination in Russia based on provincial materials and sources of counties. The main problems that resisted
the favorable fulfillment are reviewed and analyzed, such as neglect of authorities of villages, lack of medical
staff, qualification of smallpox vaccinators in Tauride province, the poor quality of the delivered detritus or
absence of lymph in general. According to the statistical Russian yearbook for the 1905-1915was created a
schedule showing the relation between the ill with smallpox and vaccinations. The gradual improvement is
described in example of Berdyansk County. According to the notes of country doctors was given an overall
assessment of provincial sanitary conditions in the second half of XIX - early XX centuries. The relations
between the local population and vaccination is shown, the Crimean Tatars are especially highlighted, who,
according to doctor”s words, actively prevented smallpox vaccination in their surroundings. The issue of the
financial component the problem is widely opened. There is information about wages of medical staff, payment
of each vaccination, the cost price of vaccinations. This article lists all providers of detritus in the Tauride
province. According to the information from county”s meetings it is discovered that calf house contaminated
with smallpox was in our region for several years. Reasons for the refusal of the provincial authorities to build
calf house in Simferopol are also described.